Cost-Effectiveness of CCTV Surveillance Systems: Evidence from a Polish City - Matczak, Piotr; Wójtowicz, Andrzej; Dąbrowski, Adam; Mączka, Krzysztof (Springer, 2022)
Closed-circuit television (CCTV) surveillance has been increasingly popular worldwide as a crime prevention measure, while its effectiveness, efficiency, and related privacy issues are debated. In this paper, we investigated whether the municipal CCTV surveillance system is cost-effective in the case study of Poznan, Poland. The analysis comprised (a) the preventive effectiveness of CCTV, (b) costs of CCTV surveillance system installation and operation, and (c) costs of crime. We collected police data on three categories of street crimes: (a) car burglary/theft, (b) car damage, and (c) robbery, as well as data on the costs of CCTV surveillance system construction and maintenance. We searched for a year after installing the CCTV system when the accumulated, hypothetical financial cost of crime was higher than the actual accumulated cost of crime and CCTV installation and maintenance in any treatment area. The number of crimes in a given category was predicted based on a comparable control area, where there were no cameras. Our study suggests that CCTV surveillance is cost-ineffective in most areas. This result implies the cautious development of CCTV surveillance, taking into account the target crime types and costs, including social costs and benefits. Evaluating cost-effectiveness, although considered as a robust measure, is in practice difficult. However, analysis of the correlation between land use characteristics and cost-effectiveness may provide practical advice on where to develop CCTV surveillance monitoring.
Keywords: Crime prevention; CCTV; Poland; Policy efficiency